Spatter and powder evolution in laser powder bed fusion of Nickel-based superalloys - Gasper, Alexander (2019)
Laser powder bed fusion (PBF-LB) technology has matured sufficiently to allow direct manufacture for a range of applications. However, there are still variabilities in processing and difficulties in qualifying parts due to defects inherent to the process. These hinder the wider adoption of the technology and its application in more demanding components, for industries such as aerospace and powder generation, where failure cannot be tolerated. The generation of spatter during processing is an aspect of the process which is considered detrimental, is inherent to the melting process, but has received minimal attention to date. The work in this thesis aims to increase understanding of the spatter particles generated, their influence on the powder in the system, and their effect on parts. This work provides an understanding of oxide and spatter formation in PBF-LB and its role throughout the process. As a result of this research, it has been established that the generation of spatter is a gas atomisation process in PBF-LB which creates a secondary powder source different from the virgin material. Therefore, current PBF-LB processing is always some combination of spatter and feedstock powder. These particles can produce critical defects, decreasing the mechanical performance of parts, and contributing to variation in the process. Therefore, it is crucial that their effect is understood.